PERCEPTION PAR LES EMPLOYÉS DU RÔLE STRATÉGIQUE DES TIC & CHANGEMENT ORGANISATIONNEL CAS DE QUELQUES ENTREPRISES ALGÉRIENNES - Djilali Benabou; Abdellatif Chelil; Soumia Tabeti (European Scientific Journal, ESJ, 2015)
The perception of the strategic role of ICT (information and communication technologies) and their impact on the content and the organizing of work is a recurring theme in many empirical and theoretical studies. However, most of them were conducted only in developed countries. Therefore, the study of the implementation of ICT in some Algerian enterprises is very important considering the major changes taking place in our country. This work is an attempt of highlighting the impact of the introduction of ICTs in the management of companies according to the perception of some Algerian business employees.